2022
DOI: 10.3390/cells11111789
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation: The Underestimated Emerging Regulators of Skeletal Muscle Physiology

Abstract: O-GlcNAcylation is a highly dynamic, reversible and atypical glycosylation that regulates the activity, biological function, stability, sublocation and interaction of target proteins. O-GlcNAcylation receives and coordinates different signal inputs as an intracellular integrator similar to the nutrient sensor and stress receptor, which target multiple substrates with spatio-temporal analysis specifically to maintain cellular homeostasis and normal physiological functions. Our review gives a brief description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 268 publications
0
10
0
Order By: Relevance
“…During low-to-moderate-intensity exercise, the main fuel sources supplying skeletal muscle are glucose and are heavily influenced by insulin and glucose utilization increases progressively with increasing exercise intensity until near maximum intensity [ 64 ]. Several recent studies have demonstrated that O -GlcNAcylation controls early glucose metabolism in skeletal muscle [ 48 , 72 , 88 , 89 ]. The fuel metabolism and energy homeostasis of skeletal muscle are greatly dependent on the glucose uptake and disposal.…”
Section: O -Glcnacylation Is An Essential Metabolic Modulato...mentioning
confidence: 99%
See 4 more Smart Citations
“…During low-to-moderate-intensity exercise, the main fuel sources supplying skeletal muscle are glucose and are heavily influenced by insulin and glucose utilization increases progressively with increasing exercise intensity until near maximum intensity [ 64 ]. Several recent studies have demonstrated that O -GlcNAcylation controls early glucose metabolism in skeletal muscle [ 48 , 72 , 88 , 89 ]. The fuel metabolism and energy homeostasis of skeletal muscle are greatly dependent on the glucose uptake and disposal.…”
Section: O -Glcnacylation Is An Essential Metabolic Modulato...mentioning
confidence: 99%
“…Meanwhile, type IIb is mainly exist in rodents, and types IIa and IIx are classified in humans [ 164 ]. It is the metabolic and morphological phenotype of each skeletal muscle fiber type coupled with the essential regulation of O -GlcNAcylation on skeletal muscle metabolic homeostasis and structural and contractile properties leading to the unique fine characteristics of O -GlcNAcylation in each type of skeletal muscle fiber [ 48 , 72 , 144 , 165 , 166 ]. In fact, the modulation of O -GlcNAcylation, OGT and OGA in each muscle fiber type is completely different, which may be attributed to the patterns of metabolic and molecular responses unique to each skeletal muscle fiber type [ 167 ].…”
Section: The Fine Characteristics Of O -Glcnacylat...mentioning
confidence: 99%
See 3 more Smart Citations